LncRNA RP11-297P16.4 Promotes the Invasion and Metastasis of Non-Small-Cell Lung Carcinoma by Targeting the miR-145-5p/MMP-2/9 Axis - Wei Wang; Yu Lu; Guang-Mei Qin; Lin-Feng Ni; Bai-Xue Xu; Chao-Feng Liu; Bao-Feng Yu; Hai-Long Wang; Min Pang (Biomedicines)
Background/Objectives: Long noncoding RNAs (lncRNAs) participate in the occurrence and development of non-small-cell lung carcinoma (NSCLC). But for certain lncRNAs, their effects on NSCLC remain unclear. This work discovered that lncRNA RP11-297P16.4 is elevated in NSCLC. Methods: LncRNA RP11-297P16.4 expression within LUAD tissues and cells was measured through RT-qPCR and Western blot. To assess the role of the lncRNA RP11-297P16.4 in NSCLC, gain- or loss-of-function experiments were conducted using an NSCLC mouse tumor model. Results: Silencing of the lncRNA RP11-297P16.4 inhibited the NSCLC cell line invasion and migration potential, but re-expression of the lncRNA RP11-297P16.4 had the opposite effect. A luciferase reporter confirmed that the lncRNA RP11-297P16.4 functions as a competitive endogenous RNA (ceRNA) through the sponge of miR-145-5p. The expression of lncRNA RP11-297P16.4 was negatively correlated to the level of miR-145-5p in NSCLC cells, which sponged miR-145-5p and suppressed tumor cell migration and invasion by targeting matrix metalloproteinase 2 (MMP-2) and MMP-9. Conclusions: Our findings suggested that the lncRNA RP11-297P16.4/miR-145-5p/MMP-2/9 regulatory axis is the key pathway for mediating the migration and invasion of NSCLC.